Comparison of Efficacy of Ferrous Sulfate and Carbonyl Iron on the Blood Film of Iron Deficiency Anemia in Pregnant Women - Ahmed, Taslima Nasreen; Shahriar, Iram; Iqbal, Jalal Uddin; Rowshan, Mahfuza Mazeda; Nahar, Sharmin; Akhter, Shakila (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Iron deficiency anemia is the most common and important public health problem all over the world in the risk group of antenatal women. Research is going on to improve the iron status of the pregnant women with different forms of iron available. In this regard Carbonyl Iron is showing promising result in improving the red cell mass with better compliance. Objective: The purpose of present study was to compare the efficacy of Ferrous Sulfate and Carbonyl Iron in the blood film of iron deficiency anemia in pregnant women. Methodology: An observational prospective study in obstetric and gynae out – patient department of Sir Salimullah Medical College and Mitford Hospital. Women between 16 – 28 weeks of pregnancy with haemoglobin level 7 – 10 gm/dl and with microcytic hypochromic blood film were included in this study. Pregnant women in 1st and 3rd trimester of pregnancy were excluded from the study. Among the study population one group was given tablet Ferrous Sulfate and another group was given capsule Carbonyl Iron. Results: At the end of study (after 12 weeks) MCV, MCH, MCHC level were more increased incase of Carbonyl Iron group than Ferrous Sulfate group which is statistically significant. Conclusion: Carbonyl Iron is more effective than Ferrous Sulfate in the treatment of iron deficiency anemia in pregnancy. J Shaheed Suhrawardy Med Coll 2021; 13(1): 46-49